AN ANALYSIS OF TRANSLATION SHIFT IN THE MERRY RIANA’S DARE TO DREAM BIG BOOK - Levi, Gerensius; Verayanti Utami, Ni Made (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
People are destined to live with pressures, and some deal with them by conducting paradoxes to survive. However, consciously or unconsciously people construct and conduct paradoxes to live. Paradox is a contradiction of two things. Winston Smith, has to run paradoxical life for the sake of surviving the pressures in Orwell’s 1984. This study examines the causes and reasons of Winston Smith committing paradoxes and the ways he applies his paradoxes to disclose his survivals against lethal pressures and compelling inner conflicts. Applying Roy Sorensen's paradox theory, supported with discourse study, within a qualitative method of study, this research analyzes the paradoxical realm of Winston Smith in his surviving the pressures. The result shows that Winston Smith conducts three kinds of paradoxes, i.e., the paradox of thoughts, the paradox of action, and the combination of the two paradoxes that contains how Winston's thoughts and actions are contradictory. It is a must for him to take the three kinds of paradoxes to survive the pressures and achieve his desires, yet, consequently, he has to experience inner conflicts